2009
DOI: 10.1007/s10151-009-0459-5
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal transplantation

Abstract: Autotransplantation in the rat is a simple technique, achieves a high rate of success and better clinical evolution than colostomy. This model may ultimately lead to research into anorectal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
12
0
9
Order By: Relevance
“…In that study, the anorectum from female pigs was transplanted into male pigs without immunosuppression and successful inferior mesenteric artery (IMA), inferior mesenteric vein (IMV), and pudendal nerve (PN) anastomoses were achieved. Since then, similar experimental studies have been reported using rat [810], swine [11], and canine models [12]. However, no reports currently exist in the literature examining the possibility of anorectal transplantation in humans.…”
Section: Introductionmentioning
confidence: 83%
“…In that study, the anorectum from female pigs was transplanted into male pigs without immunosuppression and successful inferior mesenteric artery (IMA), inferior mesenteric vein (IMV), and pudendal nerve (PN) anastomoses were achieved. Since then, similar experimental studies have been reported using rat [810], swine [11], and canine models [12]. However, no reports currently exist in the literature examining the possibility of anorectal transplantation in humans.…”
Section: Introductionmentioning
confidence: 83%
“…Histological examination revealed satisfactory inferior mesenteric flow at 24 h after surgery; however, more detailed information regarding this is unavailable. Recently, Galvão et al reported the development of a rat intestinal transplantation model (including the small and large bowel, rectum, and anus) by anastomoses of the recipient's aorta to the donor's aorta, and the donor's portal vein to the recipient's superior mesenteric vein16. Further, they succeeded in swine anorectal autotransplantation by anastomoses between the IMA and the aorta, the IMV and vena cava, and the PNs.…”
Section: Discussionmentioning
confidence: 99%
“…of all organs involved in defecation, including the perineal skin, anus, rectum, and the sphincter muscle) has strong potential as an innovative therapy for anal dysfunction. Anorectal transplantation models using rats1617 and swine1819 have been reported in experimental trials; however, these experimental systems have considerable drawbacks. Because rats and pigs do not have the capacity to inhibit defecation and habits similar to those of humans, they are not particularly useful as model subjects for human application.…”
mentioning
confidence: 99%
“…Este modelo experimental estimulou o desenvolvimento de outros modelos que contemplassem o estudo do transplante do intestino grosso em seu segmento distal, incluindo o esfíncter anal. Isso culminou na descrição de um modelo inédito de transplante autólogo anorretal em ratos, que se mostrou muito interessante para o estudo da função deste segmento, e permitiu avaliação sem a interferência da rejeição do enxerto 90 . Nesse trabalho eles comparam um modelo de transplante anorretal ortotópico, onde o ânus era posicionado em sua localização original e o heterotópico, onde o ânus era exteriorizado na parede abdominal como uma anustomia, com a ressecção do segmento anorretal e colostomia.…”
unclassified
“…Nos grupos de auto-transplante foram observados restauração da de defecação e ganho de peso logo na primeira semana de pós-operatório. Ao contrário, no grupo que sofreu colostomia, os animais mostraram complicações e altos índices de mortalidade 90 . Em modelo mais recente, animais submetidos a transplante isogênico mostraram evolução clínica semelhante às observadas nos grupos de auto-transplante 91 .…”
unclassified